Transformational Leadership in Improving Employee Integrity at Lembaga Perkreditan Desa (LPD) in Bali Province - I Nyoman Resa Adhika; I Gede Riana; I Made Artha Wibawa; Made Surya Putra (International Journal of Social Science and Business, 2023)
Growth in the number of LPDs is not followed by the amount of profit growth. There has been a decline in profit from 2020 to 2021. The decline in assets occurred by 3 percent until December 2020 compared to 2019. Meanwhile, in 2021 the decline in assets was 0.02 percent compared to 2021. A total of 130 LPDs were recorded as no longer operating. Until 2022, there are 36 LPDs experiencing legal problems due to a lack of employee integrity. This study was conducted to find answers to the question of how the influence of transformational leadership on employee integrity in LPDs in the Bali region. This study designed a quantitative approach. Quantitative analysis using structural equation model with PLS. The research was conducted in LPDs in nine regencies/cities in Bali Province with 1,437 units. The findings of this study are that the role of leadership in improving employee integrity is very important. Leadership acts as a driving force for employees so that employee integrity can be applied optimally in LPD. In building employee integrity, leaders must have a firm and straightforward commitment to support employees to apply good integrity in providing services to villagers, so that LPD can continue to develop sustainably, and employees have a sincere dedication to serving villagers.